Association of 6‐Minute Walk Performance and Physical Activity With Incident Ischemic Heart Disease Events and Stroke in Peripheral Artery Disease. Issue 7 (July 2015) - McDermott, Mary M.; Greenland, Philip; Tian, Lu; Kibbe, Melina R.; Green, David; Zhao, Lihui; Criqui, Michael H.; Guralnik, Jack M.; Ferrucci, Luigi; Liu, Kiang; Wilkins, John T.; Huffman, Mark D.; et al.
Abstract : Background: We determined whether poorer 6‐minute walk performance and lower physical activity levels are associated with higher rates of ischemic heart disease (IHD) events in people with lower extremity peripheral artery disease (PAD). Methods and Results: Five hundred ten PAD participants were identified from Chicago‐area medical centers and followed prospectively for 19.0±9.5 months. At baseline, participants completed the 6‐minute walk and reported number of blocks walked during the past week (physical activity). IHD events were systematically adjudicated and consisted of new myocardial infarction, unstable angina, and cardiac death. For 6‐minute walk, IHD event rates were 25/170 (14.7%) for the third (poorest) tertile, 10/171 (5.8%%) for the second tertile, and 6/169 (3.5%) for the first (best) tertile ( P =0.003). For physical activity, IHD event rates were 21/154 (13.6%) for the third (poorest) tertile, 15/174 (8.6%) for the second tertile, and 5/182 (2.7%) for the first (best) tertile ( P =0.001). Adjusting for age, sex, race, smoking, body mass index, comorbidities, and physical activity, participants in the poorest 6‐minute walk tertile had a 3.28‐fold (95% CI 1.17 to 9.17, P =0.024) higher hazard for IHD events, compared with those in the best tertile. Adjusting for confounders including 6‐minute walk, participants in the poorest physical activity tertile had a 3.72‐fold (95% CI 1.24 to 11.19, P =0.019) higher hazard for IHD events, compared with the highest tertile. Conclusions: Six‐minute walk and physical activity predict IHD event rates in PAD. Further study is needed to determine whether interventions that improve 6‐minute walk, physical activity, or both can reduce IHD events in PAD.